INITIAL BREEDING MATERIAL FOR DEVELOPMENT OF PEA VARIETIES IN THE KUBAN - O. V. Alikina; A. G. Besedin (Овощи России)
Results of two yeaґs field studying of 522 samples of peas are presented. Twenty-five samples with valuable agronomic traits were selected for further breeding program. Correlation between duration of interstage periods was revealed.